The role of the dorsolateral prefrontal cortex in retrieval from long-term memory depends on strategies: a repetitive transcranial magnetic stimulation study - Manenti, R.; Cotelli, M.; Calabria, M.; Maioli, C.; Miniussi, C. (Neuroscience, 2010)
The ability to associate a name to a face is a crucially relevant task in daily life. In this study, we investigated the neuronal basis of face-name retrieval in young subjects using repetitive transcranial magnetic stimulation (rTMS) over the left or right dorsolateral prefrontal cortex (DLPFC). The experimental task was composed of two study phases: an encoding phase and a retrieval phase. During the encoding phase, subjects saw a face (familiar or unfamiliar) followed by a name. During the retrieval phase, they saw the face together with two names and had to choose the name that was correctly associated with the face. rTMS was delivered only during retrieval. In addition, we evaluated the use of memory strategies during the task. Accordingly, subjects were subdivided into two groups: strategy users (SU) and no-strategy users (NSU). No rTMS effects were present for familiar face-name pairs, probably due to a ceiling effect. However, for unfamiliar face-name pairs, the different use of memory strategies resulted in different rTMS effects. The SU group showed a selective interference effect after right DLPFC stimulation, whereas the NSU group showed an effect after left DLPFC stimulation. Importantly, the overall performance of the two groups was comparable. We suggest that during memory retrieval the left DLPFC might be recruited when the subject does not apply deliberately a retrieval strategy whereas there is a shift to the right DLPFC if cognitive control processes that are engaged by strategies are needed to guide episodic retrieval.